Using Digital Technology for Learning Quality: Descriptive Study at Junior High Schools in Mojokerto - Ruslan Affandi; Murtadhlo Murtadhlo; Amrozi Khamidi (IKIP Widya Darma Surabaya, 2026)
Objective: The use of digital technology is becoming increasingly widespread in Indonesian high schools through various strategies. This research aims to find out the forms or strategies of using digital technology along with its impact on learning. Method: Descriptive qualitative was used to analyse various findings at public junior high school 1 Bangsal and public junior high school 2 Gedeg Mojokerto. Purposive sampling was applied with data collected through interviews, observations and documentation to fulfil triangulation. Results: This research found that there are differences in the implementation of digital technology at public junior high school 1 Bangsal and public junior high school 2 Gedeg Mojokerto in terms of teaching practices and methods, as well as for activities like curriculum development and programme evaluation. Both schools still showed an overall improvement in learning outcomes ranging from 12-18%. Novelty: A review is being conducted on the effects of implementing various types of digital technology related directly or indirectly to learning from the perspective of those directly involved in both schools, which has yet to examine the success and challenges faced.